Réponses

2013-11-01T15:50:58+01:00
A= (5x² - 2x-5x+2) - (6-6x-3x+3x²)
A= 5x² - 7x + 2 + 6 + 9x + 3 x²
A = 8x²+2x+8

2013-11-01T15:57:45+01:00
A = (x - 1) * (5x - 2) - (-6 + 3x) * (-1 + x)
A = x * 5x - x * 2 - 1 * 5x - 1 * 2 - (-6) * (-1) + (-6) * x + 3x * (-1) + 3x * x
A = 5x² - 2x - 5x - 2 - 6 + (-6)x + (-3)x + 3x²
A = 8x² - 16x - 8

B = -(3x - 8) * (x + 4) - (7x - 8) * (-1 + 7x)
B = -3x * x + (-3x) * 4 - 8 * x + 8 * 4 - 7x * (-1) + 7x * 7x - 8 * (-1) + (-8) * 7x
B = -3x² + (-12x) - 8x + 32 + 7x + 49x² + 8 - 56x
B = 46x² - 69x + 40

C = -(2x - 5) * (3 - 4x) + (6x - 9) * (-2x - 1)
C = -2x * 3 - (-2x) * (-4x) - 5 * 3 - 5 * (-4x) + 6x * (-2x) - 6x * (-1) - 9 * (-2x) - 9 * (-1)
C = -6x - 8x² - 15 - (-20x) + (-12x²) + 6x + 18x + 9
C = - 20x² - 2x - 6
Ouah! Merci beaucoup! :D
Je t'en prie, ça fait plaisir :3.